Clinical Function Improves After Subacromial Injection of Local Anesthetic in Full-Thickness Rotator Cuff Tears: A Randomized Control Trial. Issue 1 (2nd January 2020) - Forsythe, Brian; Agarwalla, Avinesh; Puzzitiello, Richard N.; Patel, Bhavik H.; Lu, Yining; Verma, Nikhil N.; Romeo, Anthony A.; Cole, Brian J.
Background: Rotator cuff pathology is the most common cause of shoulder pain in adults, accounting for nearly 70% of shoulder-related visits to clinicians. However, physical examination findings may be limited because of pain or patient inhibition. Purpose: To establish whether a relationship exists between pain, range of motion, and strength in patients with a full-thickness rotator cuff tear. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A single-blind, randomized controlled study of 40 patients undergoing rotator cuff repair for full-thickness rotator cuff tears was performed. Patients were randomized to receive either a subacromial 10-mL 2% lidocaine injection or a sham injection, with no contents being injected into the subacromial space. Before the injection, patients were assessed using a visual analog scale for pain (VAS-Pain) as well as the Constant-Murley subjective questionnaire and objective physical examination. The examination was repeated 10 minutes after injection and 6 months postoperatively. VAS-Pain after injection was not assessed. The assessment at 6 months was performed to demonstrate improvement of rotator cuff function after operative management. Statistical analysis included Student t and chi-square tests as well as multivariate binomial logistic regression analyses to identify predictors for improvement after injection. Results were considered significant if P < .05. Results: Range of motion, strength, and Constant-Murley score significantly improved after a subacromial lidocaine injection ( P < .05). Range of motion, strength, Constant-Murley score, and VAS-Pain significantly improved at final follow-up compared with the preinjection assessment for both groups ( P < .05); however, there was no difference ( P > .05) between groups at 6 months postoperatively. Conclusion: After subacromial lidocaine injections, patients exhibited modest but significant improvements in range of motion, strength, and the Constant-Murley score. Pain may limit range of motion and strength in patients with full-thickness rotator cuff tears independent of the mechanical impact of the tear itself. Registration: NCT02693444 (ClinicalTrials.gov identifier).